The Impacts of Two Adaptive Auditory–Cognitive Training Paradigms on Listening to Competing Talkers - Fisher, Charlie; Johns, Michael A.; Decruy, Lien P.; Calloway, Regina C.; Dunlap, Jason L.; Simon, Jonathan Z.; Anderson, Samira; Kuchinsky, Stefanie E. (Seminars in Hearing, 2025)
Speech intelligibility among competing talkers becomes more difficult with age, even for older adults with clinically normal hearing. Recently, there has been a growing interest in the implementation of auditory–cognitive training to improve speech-in-noise recognition performance, particularly for older adults. In this study, we implemented two levels of cognitive demand in an adaptive auditory–cognitive training program that used a competing-speaker paradigm. Older adults with normal to near-normal hearing thresholds were assessed on training performance (at the individual and group level), self-reported training strategies, and far-transfer learning in a speech-perception-in-noise task. Training performance analysis revealed that some older adults, particularly those in the more demanding training, performed poorly during the auditory–cognitive training itself. Some participants in this group reported disengagement, potentially due to the low level of those individuals' self-reported satisfaction with engaging in challenging tasks in daily life. Despite these challenges, however, both groups generally improved in the far-transfer learning assessment, though there was variation among participants. Our results suggest that too-high levels of cognitive demand within the auditory–cognitive training may limit some aspects of training outcomes for speech perception in noise; however, higher cognitive demand may be beneficial for those who enjoy challenging tasks.
Keywords: auditory training; older adults; competing speakers; cognitive load; individual differences